HUBUNGAN ANTARA GAME DAN PUSTAKAWAN SEBAGAI SARANA EDUKASI PEMUSTAKA - Nugroho, Prasetyo Adi (Jurnal Al- Ma'arif : Ilmu Perpustakaan dan Informasi Islam, 2024)
Librarians play an important role in improving literacy. Literacy improvement programs require quite a lot of funds and resources. Games can be a means of increasing reader literacy. This study aims to observe citations and words that are widely used in abstracts and titles of previous research regarding the use of games by librarians. This study uses a quantitative method called bibliometrics to collect and analyze data. Data was taken from the Scopus website as many as 117 from 1981-2023. Data were analyzed using R Studio software. The results show that most of the documents cited were written by authors from European countries and the United States. However, none of this previous research was cited by fellow local authors. The results above also show that the words that are often used in both the title and abstract of previous research include the word health.